Designing an English syllabus for the third year students at FLD, Nghe An Teacher Training College. M.A Thesis Linguistics: 60 14 10 - Thái, Thị Mai Liên (ĐHNN, 2017)
The study aims to have a deep understand into the student’s needs and teacher’s ability concerning English Literature. It draws the experiences of ex-students and the situation of teaching and learning English Literature at NA TTC. It also carries a hope to build an English Literature syllabus for the last year students in FLD at NA TTC from the detailed aspects of aims and objectives of the course, contents of the lectures as well as teaching methodology and assessment. The syllabus is designed for a three-month teaching time (15 weeks) with a schedule of two hours per week per class. The syllabus mainly focuses on the contents of the syllabus. This should be the most important for the subject. It is not only a “day-to-day guide to the teacher” but also the specification of “what is to be taught and in what order” (Prabhu, 1984).